Hydroponics: An Alternative Method for Root and Shoot Classification on Sugarcane Genotypes - Chanoknat Chapae; Patcharin Songsri; Nuntawoot Jongrungklang (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
A hydroponic system was considered to be an appropriate method for root investigations, particularly if the method can be established as a screening technique to classify differences in root traits among sugarcane lines. The aim of the research was to classify root and shoot characters of sugarcane lines grown under hydroponic conditions and to investigate their correlation with the field measurements. Hydroponic and field tests used a randomized complete block design (RCBD). Eight elite sugarcane lines were assigned as treatments. Shoot and root traits were measured at 3 months after transplanting in the hydroponic experiment, and field trial measured root length density (RLD) at 4 months after planting. Root and shoot traits under the hydroponic system showed significant differences among sugarcane lines. KK3 had a high root surface area, root volume, root length and root dry weight and TBy27-1385 demonstrated a high stem height and stem dry mass. Moreover, root dry weight, root volume and root surface area positively correlated with shoot dry mass. Positive correlation was exhibited between root traits such as dry weight of root and root length derived from hydroponic studies and RLD derived from field conditions.